Analisis Jumlah Klaim Agregasi Berdistribusi Negative Binomial Dan Besar Klaim Berdistribusi Discreate Uniform Dengan Menggunakan Metode Konvolusi - Seftina Diyah Miasary; Fara Lukita Umul Amaliah; Emy Siswanah (Program Studi Matematika Universitas Sulawesi Barat, 2022)
Claims are a form of demands from insurance policy holders in order to get protection against financial losses due to risks that occur. Claims that arise every time a risk occurs are called individual claims, while the total of individual claims during an insurance period is called aggregation claims. In addition, claims are one of the important elements in optimizing the minimum expenditure of insurance companies where one of the calculations that insurance companies need to know based on claims is aggregate loss. Aggregate loss is the total loss in a period experienced by the policyholder which is borne by an insurance company. This study aims to determine the estimated total aggregate loss claims for the number of claims with a Negative Binomial distribution and the size of the claims with a Discrete Uniform distribution in the recapitulation of claim payments according to all types of guarantees and the nature of injuries in 2018-2020 PT. Jasa Raharja, Purwakarta. This study uses the convolution method with the help of Easyfit and R Studio software. The convolution method is a method of calculating the number of multiplication pairs of a probability density function. The results of this study indicate that from the recapitulation data on claim payments according to all types of insurance and nature of injury in 2018-2020 PT. Jasa Raharja, Purwakarta, the estimated total monthly aggregate loss claims for the years 2021-2023 using Jasa Raharja's insurance claim data from 2018 to 2020 based on the Negative Binomial distribution and the Discrete Uniform distribution is IDR 4,278,5545,000 and the variance value of 2.128412e-06.